Local Wisdom-Based Digital Comics for Enhancing Critical Thinking on the Water Cycle in Fifth-Grade Elementary School Students - Suharta, Firyal Dwi Ezrina; Syamsi, Atikah; Atikoh, Nur; Syafiudin, Mohammad (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2025)
This study was motivated by the need for students and teachers for interesting learning media that can improve students' critical thinking skills. This study aims to determine how the process of developing local wisdom-based digital comic media on water cycle material, determine the feasibility of local wisdom-based digital comics on water cycle material, determine the improvement of critical thinking skills on water cycle material through digital comic media, determine the practicality of local wisdom-based digital comic media on water cycle material. The research method used in this research is the ADDIE type Research and Development research method which consists of five stages, namely, Analyze, Design, Development, Implementation, and Evaluation. The results showed that the development of local wisdom-based digital comics starts from analyzing needs, then developing comics using the Corel Draw x7 and Canva applications by determining the storyline, characters, characters, material and cover on the comic , digital comics were tested for feasibility from media validators of 89% with a very feasible category, obtained a percentage of feasibility from material validators of 78% with a feasible category, and obtained a percentage of feasibility from language validators of 93% with a very feasible category. , then the N-Gain test is analyzed by obtaining the average N-Gain result of 0.78, which means that the N-Gain score is in the high category and the N- Gain Percent shows 78.26, which means it is in the effective category. the response of the fifth grade homeroom teacher having a percentage of 95% and there was an assessment of student responses having a percentage of 83%. it can be concluded that the practicality of digial comics meets the criteria of being very valid or very practical as a learning medium.